Comparative study of ambient air quality (Pm2.5, No2, So2) and lung function performance among college students / Nurul Syuhada Abd Hamid - Abd Hamid, Nurul Syuhada (2011)
Background: A comparative cross-sectional study was done to assess lung function performance and the current ambient air quality in two areas as consequences of exposure to traffic pollution. The locations selected were college that is situated at urban (Damansara) and suburban (Puncak Alam) area. To observe the effects, college students from both areas were being taken as study respondents. Methods: Numbers of parameters were selected during this study including the concentration of air pollutants Particulate Matter 2.5 (PM2.5), Nitrogen Dioxide (NO2) and Sulphur Dioxide (SO2). The pollutants concentration is measured at both locations for 1 hour for NO2 and SO2 and 24 hour for PM2.5 using EVM7 (Quest). Lung function test have been done to 90 respondents (N=90) at both locations using Spirometer (Vitolgraph) to identify their lung performance status (FVC, FEV1. FEV1/FVC). To the same respondents, questionnaires also being distributed to obtain their feedback about air quality and current health status based on self diagnose approach. The relationship between air pollutants concentration and lung function performance is analyzed using SPSS version 17.0 to search for the significances. Results : Result shows that there is significance different of the pollutants concentration between the study locations (p < 0.05) on two parameters which are PM2.5 and NO2. Significant difference also existed between the lung function performances in urban and suburban areas (p=0.001 ). Among three data taken for lung function performance, FVC% and FEV% shows significance different with p value each are 0.002 and 0.005. Inversely proportional relationship between FEV1 % with PM2.5 (p= 0.028) and FEV1 % with NO2 (p=0.044) which means the higher the concentration of PM2.5 and NO2, the poorer the lung function performance in the locality. Respondents self diagnosis questionnaire shows significance different in two short term effects being asked, which is eye irritation (p=0.0012) and dizziness (p=0.017). Among three parameters measured, only PM2.5 concentration exceeds the EPA standards, while the rest, are below the RMAQG standards. Conclusion: Study found out that students in urban area are exposed to higher concentration of ambient air pollutants compare to students in suburban area and showed a decrease in their lung function performances.